PENGARUH PENERAPAN PEMBELAJARAN TARI KREASI TERHADAP KEMAMPUAN MOTORIK KASAR SISWA TUNAGRAHITA DI SEKOLAH DASAR LUAR BIASA - Rahajeng Ratnayanti; Usep Kustiawan (Jurnal ORTOPEDAGOGIA, 2014)
This research were to describe: (1) the gross motor capability of the student with intellectual disability in SDLB Putra Jaya before intervention (A). (2) while intervention (B). (3) after intervention (A’) (4) the differences of the gross motor capability of the student with intellectual disability in SDLB Putra Jaya between before and after intervention. The result of the research were (1) change level baseline condition (A) = +17,85%;(2) change level intervension condition (B) = +17,86%;(3) change level baseline condition baseline (A’) = +3,58%; (4) change level intervension (B) condition toward baseline condition (A) = +3,57%; (5) change level baseline (A’) condition toward intervension condition (B) = -17,86%. There weren’t any overlapping data among them (0%).   Penelitian ini bertujuan untuk mendeskripsikan: (1) kemampuan motorik kasar siswa tunagrahita di SDLB Putra Jaya sbelum intervensi (A). (2) selama intervensi (B). (3) setelah intervensi (A’) (4) perbedaan kemampuan motorik kasar siswa tunagrahita di SDLB Putra Jaya antara sebelum dan sesudah intervensi. Hasil penelitian ini adalah (1) change levelkondisi baseline(A) = +17,85%;(2) change level kondisi (B) = +17,86%;(3) change levelkondisi (A’) = +3,58%; (4) change levelkondisi (B) terhadap change levelkondisi (A) = +3,57%; (5) change levelkondisi (A’) terhadap change levelkondisi (B) = -17,86%. Overlapping antar kondisi tidak ada di antara data tersebut (0%)